PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN SERPONG KOTA TANGERANG SELATAN - Sanusi; Dhasa Eka, Priehadi (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work discipline and motivation on workforce performance at the Serpong District Office, South Tangerang City. The method used is quantitative. The sampling technique used saturated sampling and a sample of 70 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that: There is a positive and significant influence between Work Discipline (X1) on Employee Performance (Y) at the Sepong District Office, South Tangerang City, this can be proven from the calculated t value > t table 5,091 > 1.996 with a significant level 0,000 < 0,o5 or thus Ha1 is rejected and Ho1 is accepted. There is a positive and significant influence between Motivation (X2) on Employee Performance (Y), at the Serpong District Office, South Tangerang City, this can be proven from the calculated t value > t table 8.870 > 1.996 with a significant level of 0,000 < 0,05 or so Ha2 is rejected and Ho2 is accepted. Simultaneously there is a positive and significant influence on Work Discipline (X1) and Motivation (X2) on Employee Performance (Y) at the Serpong District Office, South Tangerang City, this can be proven from the obtained value of f calculated > f table or 47.604 > 3 .13 with a significant level of 0,000> 0,05 or thus Ho3 is rejected and Ha3 is accepted. This research confirms the existence of a positive and significant influence between work discipline, motivation and performance of employees at the Serpong District Office, South Tangerang City.